Peningkatan Keterampilan Berbicara melalui Pendekatan Proses Siswa SMA Negeri 16 Bone - Muh. Safar; Ihramsari Akidah; Andi Srimularahamah; Tuti Wijayanti (Departement of Mathematics Education, 2023)
This study aims to describe speaking skills through a process approach for class X students of SMA Negeri 16 Bone. The type of research used is classroom action research. While the approach used in this research is descriptive qualitative. This research consists of two cycles. Each cycle consists of two meetings. The research subjects were class X students of SMA Negeri 16 Bone, totaling 36 students consisting of 16 boys and 20 girls. The research focus of class X students on speaking skills with a process approach. Data collection techniques using observation techniques, tests and documentation. The data analysis technique used is descriptive qualitative. The results showed that the value of the speaking skills of class X students of SMA Negeri 16 Bone with the process approach increased from cycle 1 to cycle 2. This research proved that the use of the process approach in teaching speaking could improve the speaking skills of students of class X SMA Negeri 16 Bone.